Exploring the relationship between motivation types, goal orientations, and athletic toughness dimensions among Universiti Kebangsaan Malaysia (UKM) athletes - Zamri, Zamil Haziq; Nazarudin, Mohamad Nizam (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problem: The problem addressed in this study is the lack of comprehensive research exploring the relationship between motivation types, goal orientations, and toughness dimensions in university athletes. Purpose: The purpose of this research is to investigate the correlation between different types of motivation (intrinsic, extrinsic, and amotivation) and the dimensions of athletic toughness (mental, emotional, and bodily toughness) among Universiti Kebangsaan Malaysia (UKM) athletes. Additionally, this study examines how ego orientation and task orientation influence these toughness dimensions. Methods: This study employed a quantitative research design with a sample of 100 student-athletes from UKM who participated in the 2024 SUKIPT games. Data were collected using three standardized instruments: the Sport Motivation Scale (SMS), the Mental, Emotional, and Bodily Toughness Inventory (MeBTough), and the Task and Ego Orientation in Sport Questionnaire (TEOSQ). Pearson correlation analysis was conducted to explore relationships between variables. Instrument reliability was confirmed through Cronbach’s alpha, with coefficients ranging from 0.79 to 0.85. Results: The findings reveal that intrinsic motivation strongly correlates with all toughness dimensions (mental r = 0.64, emotional r = 0.65, bodily r = 0.67), while extrinsic motivation exhibits moderate correlations (mental r = 0.53, emotional r = 0.51, bodily r = 0.49). Amotivation shows negative correlations with toughness dimensions (mental r = -0.50, emotional r = -0.49, bodily r = -0.51). Additionally, ego orientation has a moderate correlation with bodily toughness (r = 0.44), whereas task orientation exhibits weak correlations with toughness dimensions. Conclusion: This study highlights the pivotal role of intrinsic motivation in enhancing mental, emotional, and bodily toughness among athletes, while extrinsic motivation provides moderate support, and amotivation negatively impacts resilience. Ego orientation contributes more to physical resilience compared to task orientation. These findings emphasize the need for tailored interventions focusing on intrinsic motivation and balanced goal orientations to foster holistic athletic toughness.